Proposal and clinical application of molecular genetic risk scoring system, "MRplus", for BCR-ABL1 negative pediatric B-cell acute lymphoblastic leukemia- report from a single centre. (December 2021) - Gupta, Sanjeev Kumar; Bakhshi, Sameer; Kamal, Vineet Kumar; Gupta, Ritu; Sharma, Preity; Pushpam, Deepam; Sahoo, Ranjit Kumar; Sharma, Atul
Highlights: 'MRplus' risk-score is being proposed for the risk-stratification in childhood B-ALL. The integrated molecular genetic risk-score 'MRplus' can identify distinct subgroups in B-ALL. 'MRplus' score can risk-stratify B-ALL patients at baseline into those with good, intermediate and poor outcomes. Abstract: Introduction: We propose "MRplus", a molecular genetic risk score and check its clinical application in the risk-stratification of pediatric B-ALL. Methods: The genomic DNA of untreated pediatric BCR-ABL1 negative B-ALL patients was analyzed for deletions of IKZF1, PAX5, CDKN2A/B, BTG1, RB1, ETV6, EBF1, ERG, pseudoautosomal region(PAR) genes using multiplex ligation-dependent probe amplification, along with the routine genetic work-up. The patients were assigned an 'M'score- 0 (M0) for low and 1 (M1) for high genetic-risk as per the criteria by Moorman et al., and another score "IKplus"-1 (IKplus1) for IKZF1plus as per the criteria by Stanulla et al., and 0 (IKplus0) for other patients. The final "MRplus" risk-score of 0 (MRplus0), 1 (MRplus1) or 2 (MRplus2) was obtained by adding both these scores. The association of risk scores with overall survival (OS) and event free survival(EFS) was seen using Cox proportion hazard model. The overall goodness of fit of the model was done using Cox-Snell residuals. Results: The median age of 320 patients was 6 years (1−18 years). The patients with score M1 were 139 (43.4 %), M0−181 (56.6 %); IKplus1−32 (10 %) and IKplus0−288 (90 %). The final "MRplus" score of 0, 1, or 2 was obtained in 181(56.6 %), 107(33.4 %) and 32(10 %) patients respectively. The post-induction remission rate was 90.7 %, 77.8 %, 73.9 % (p = 0.004); 4-year OS 67 %, 48 %, 27 % (p < 0.001); and 4-year EFS 56 %, 34 %, 19 %(p < 0.001) in patients with "MRplus" score 0, 1, and 2 respectively. Conclusions: The proposed "MRplus" scoring at baseline could identify three distinct risk groups-good (MRplus0), intermediate (MRplus1) and poor (MRplus2), with different outcomes; in pediatric BCR-ABL1 negative B-ALL. This may help in better risk-stratification and selection of patients for alternative treatment approaches.